Modulatory Effects of Hydatid Cyst Fluid on a Mouse Model of Experimental Autoimmune Encephalomyelitis - Maryam Hajizadeh; Aynaz Jabbari; Adel Spotin; Seyyed Sina Hejazian; Tahereh Mikaeili Galeh; Hadi Hassannia; Maryam Sahlolbei; Abdol Sattar Pagheh; Ehsan Ahmadpour (Veterinary Sciences, 2024)
The reduced burden of helminth parasites in industrialized countries is probably one of the reasons for the increased prevalence of autoimmune disorders such as multiple sclerosis (MS). The current study aimed to evaluate the potential preventive effects of hydatid cyst fluid (HCF) on the disease severity in an EAE mouse model of MS. EAE-induced mice were treated with HCF before and after EAE induction. An RT-PCR-based evaluation of IFN-γ, IL-1β, TNF, T-bet, IL-4, GATA3, IL-17, RoRγ, TGF-β, and FOXP3 expression levels in splenocytes and an ELISA-based analysis of IFN-γ and IL-4 levels in cell culture supernatant of splenocytes were performed. Histopathological examinations of mice during the study were also conducted. The expression levels of T-bet, IL-4, GATA3, TGF-β, and FOXP3 in EAE + HCF mice were significantly higher compared to EAE + PBS mice. In the EAE + HCF group, the expression levels of IFN-γ, IL-1β, and TNF were significantly lower than in the EAE + PBS group. The histopathological results showed significantly reduced inflammation and demyelination in EAE + HCF mice compared to EAE + PBS mice. Our study provides proof-of-concept in the EAE mouse model of MS that helminth-derived products such as HCF have a potential prophylactic effect on MS development and present a novel potential therapeutic strategy.